Recurrent Levamisole-Induced Agranulocytosis Complicated by Bowel Ischemia in a Cocaine User - Khan, Mohammad Saud (Am J Case Rep, 2018)
Patient: Male, 59 Final Diagnosis: Levamisole induced agranulocytosis Symptoms: Abdominal pain • fever Medication: — Clinical Procedure: — Specialty: Critical Care Medicine OBJECTIVE: Challenging differential diagnosis BACKGROUND: Levamisole is a common adulterant of cocaine and up to 69% of seized cocaine in United States contains levamisole. It is a synthetic imidazothiazole derivative which was previously used as an immunomodulating agent for treatment of various connective tissue disorders and colorectal carcinoma. However, it was withdrawn later from the market due to significant toxicity associated with it. CASE REPORT: We present the case of a 59-year-old male patient with a history of active cocaine use who presented to the hospital with febrile neutropenia and agranulocytosis. He underwent extensive work-up for neutropenia and was suspected to have it secondary to levamisole-adulterated cocaine. He was treated with antibiotics and granulocyte-stimulating factor. His white cell count improved and he was discharged home. He continued to use cocaine after discharge from the hospital. He returned to the hospital 3 weeks later with recurrent neutropenia and agranulocytosis complicated by septic shock and bowel necrosis which required prolonged antibiotics and a bowel resection. CONCLUSIONS: Levamisole-induced agranulocytosis should be considered in patients who present with neutropenia and a history of cocaine use. Physicians should have high clinical suspicion and consider it a potential etiology of agranulocytosis when other causes have been excluded.